Iron deficiency and anemia in pediatric dilated cardiomyopathy are associated with clinical, biochemical, and hematological markers of severe disease and adverse outcomes - Luxford, Jack C; Casey, Charlene E; Roberts, Philip A; Irving, Claire A (The Journal of heart and lung transplantation, 2024)
There is limited evidence regarding the prevalence and impact of iron deficiency (ID) in children with dilated cardiomyopathy (DCM). Retrospective single-center review of all children between 2010 and 2020 with a diagnosis of DCM and complete iron studies. ID was defined as ≥2 of ferritin <20 μg/liter, iron <9 μmol/liter, transferrin >3 g/liter, or transferrin saturation (TSat) <15%. Clinical and laboratory indices and freedom from a composite adverse event (CAE) of mechanical circulatory support (MCS), heart transplant, or death were compared between children with and without ID. Of 138 patients with DCM, 47 had available iron studies. Twenty-nine (62%) were iron deficient. Children with ID were more likely to be receiving inotropes (17, 59%, p = 0.005) or invasive/noninvasive ventilation (13, 45%, p = 0.016) than those who were iron replete. They had a higher incidence of anemia (22, 76%, p = 0.004) and higher NT-proBNP (1,590 pmol/liter, IQR 456-3,447, p = 0.001). Children with ID had significantly less freedom from the CAE at 1-year (54% ± 10%), 2-years (45 ± 10), and 5-years (37% ± 11%) than those without (p = 0.011). ID and anemia were the only significant predictors of the CAE on univariate Cox regression. ID is highly prevalent in children with DCM. Iron studies are undermeasured in clinical practice, but ID is associated with severe heart failure (HF) and an increased risk of the CAE. The need for iron replacement therapy should be considered in children who present in HF with DCM.